Measuring transferability issues in machine-learning force fields: the example of gold–iron interactions with linearized potentials. Issue 2 (28th December 2020) - Benoit, Magali; Amodeo, Jonathan; Combettes, Ségolène; Khaled, Ibrahim; Roux, Aurélien; Lam, Julien
Abstract: Machine-learning force fields have been increasingly employed in order to extend the possibility of current first-principles calculations. However, the transferability of the obtained potential cannot always be guaranteed in situations that are outside the original database. To study such limitation, we examined the very difficult case of the interactions in gold–iron nanoparticles. For the machine-learning potential, we employed a linearized formulation that is parameterized using a penalizing regression scheme which allows us to control the complexity of the obtained potential. We showed that while having a more complex potential allows for a better agreement with the training database, it can also lead to overfitting issues and a lower accuracy in untrained systems.